DETECTING AND RESTORING GAPS AMONG FOREST PATCHES: AN ACHIEVABLE AND REPLICABLE PROPOSAL TO BOOST THE LANDSCAPE CONNECTIVITY - Bortoleto, Ludmila Araujo [UNESP]; Rodgers, John; Silva, Alexandre Marco da [UNESP] (Sciendo, 2022)
It is well known that one of the main impacts caused by land cover change is the process of forest fragmentation. Connecting the remaining fragments is always an exercise for technicians and academics, and even corridors of remaining vegetation usually present places of forest discontinuity, lacking connection strategies for the corridor to gain a real function. In this paper, we applied a model structured to identify priority locals to implement connectors. We used a GIS package and a digital, georeferenced satellite image. We complemented the project by surveying a database through a drone-based field survey. The integration of data revealed that for our studied area (Sorocaba, SP Brazil) 42.5% need assisted restoration. The mapping also revealed the existence of 25 forest fragments larger than 50 ha, arranged chiefly in one single corridor but disconnected from each other. Hence, through the application of the model, we could localize nine strategic locations in distances as short as possible among the fragments, feasible to implement a connector with the economy of resources and expect satisfactory performance in ecological terms. The database generated by the drone-based survey helped us to assert the effectiveness of the model in choosing areas that require assisted restoration to re-establish the connection of the landscape.
Keywords: ecological connectivity; connector selection methods; ecological connectors; matrix permeability; wildlife corridors